Pemanfaatan Pekarangan Rumah untuk Budidaya Sayur Sebagai Tambahan Sumber Pangan Keluarga dengan Teknik Tabulampot dan Verikultur - Fahruddin Fahruddin; Ananda Wahyu Riskikananti (Pascasarjana Universitas Mataram, 2021)
The increasing population demands more food supplies. Fulfilling the needs can be done by each households. One of the way to fulfill it is to grow vegetables on house garden or yard. The garden can be a patch of land around your house, it can be in the front side, left, right or back side of the house. However one of the main problem, the land can be too narrow. This program is held at Bung Hatta II Street, Number 21 as the chosen location to be an example for people around East Majeluk, Pejanggik. The methods used in this Program are Survey, counseling and discussion. From the activities we’ve done, we can conclude that citizens around the households have knowledge about the plant cultivation techniques using tabulampot and verticulture methods and some citizens have already started to take advantages of their garden to start the cultivation